THE CORRELATION BETWEEN SELF-EFFICACY AND INNOVATIVE WORK BEHAVIOUR IN THE EMPLOYEES OF TOURISM INDUSTRY IN A TOURISM CITY - Seger Handoyo; Yudha Prasetya Christianto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Background: Innovative work behaviour is one of the keys in order to increase the work productivity of the employees in tourism industry. This is due to the self-efficacy has a correlation to the innovative work behaviour.